2020
DOI: 10.1007/s00259-020-05025-0
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI in prostate cancer: a systematic review and meta-analysis

Abstract: Aim In recent years, the clinical availability of scanners for integrated positron emission tomography (PET) and magnetic resonance imaging (MRI) has enabled the practical potential of multimodal, combined metabolic-receptor, anatomical, and functional imaging to be explored. The present systematic review and meta-analysis summarize the diagnostic information provided by PET/MRI in patients with prostate cancer (PCa). Materials and methods A literature search was conducted in three different databases. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 63 publications
2
64
1
1
Order By: Relevance
“…The ability of both [ 18 F]DCFPyL PET/MRI and mpMRI to detect locally advanced disease was low with sensitivities of 35.29% and 41.18%, respectively. This under-staging for mpMRI and [ 18 F]DCFPyL PET/MRI is in line with previous reports [17,31]. One retrospective study by Muehlematter et al on 40 consecutive patients receiving both [ 68 Ga]Ga-PSMA-11 PET/MRI and mpMRI prior to RARP reported on a patientspecific sensitivity of detecting locally advanced disease of 69% vs. 46% (p = 0.04) and a specificity of 67% and 75% (p = 0.19) [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ability of both [ 18 F]DCFPyL PET/MRI and mpMRI to detect locally advanced disease was low with sensitivities of 35.29% and 41.18%, respectively. This under-staging for mpMRI and [ 18 F]DCFPyL PET/MRI is in line with previous reports [17,31]. One retrospective study by Muehlematter et al on 40 consecutive patients receiving both [ 68 Ga]Ga-PSMA-11 PET/MRI and mpMRI prior to RARP reported on a patientspecific sensitivity of detecting locally advanced disease of 69% vs. 46% (p = 0.04) and a specificity of 67% and 75% (p = 0.19) [15].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, PSMA-PET/MRI enables wholebody staging at a lower radiation dose, and can guide prostate biopsies in a single hospital visit, which is advantageous over performing both a pre-biopsy mpMRI and a staging PSMA PET/CT. This is the largest prospective study investigating the value of PSMA-PET using [ 18 F]DCFPyL combined with MRI compared to that of mpMRI alone [16,17]. In this, we compared tumour localization and local tumour staging of both imaging modalities to the gold standard, i.e., tumour localization and tumour stage determined in the radical prostatectomy specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Multi parametric MRI clearly stands out on the basis of strong evidence for pre biopsy evaluation and the role of PSMA PET/CT as a staging modality in localized prostate cancer is rising. The advantage of PET/MRI lies in the fact that it combines two of these excellent imaging modalities and MRI offers better soft tissue definition than CT. Areas where we could see its emerging role would be in oligometastatic disease and high-risk disease where the ability to identify more lesions would have a significant impact on the treatment approach (83). PET/MRI, therefore, has promising implications in the diagnosis and staging of prostate cancer but needs further validation in terms of research and logistics to be of primetime use.…”
Section: Discussionmentioning
confidence: 99%
“…In PCa, PET/MR can be performed by diverse radiopharmaceutical agents [25,26]. A recent meta-analysis showed that PSMA PET/MR has a higher pooled detection rate for the identification of biochemical recurrence as compared to Choline PET/MR (81.8% vs. 77.3%, respectively), independently from the PSA range [26].…”
Section: Discussionmentioning
confidence: 99%
“…In PCa, PET/MR can be performed by diverse radiopharmaceutical agents [25,26]. A recent meta-analysis showed that PSMA PET/MR has a higher pooled detection rate for the identification of biochemical recurrence as compared to Choline PET/MR (81.8% vs. 77.3%, respectively), independently from the PSA range [26]. However, the highest difference in detection rate, between 18F-Choline and 68 Ga-PSMA PET/MR, was found for PSA level < 1 ng/mL (42.86% vs. 75%, respectively) [2,27].…”
Section: Discussionmentioning
confidence: 99%